APLIKASI GURILAPSS DI ANDROID SEBAGAI STRATEGI PEMASARAN PARIWISATA KABUPATEN SUKABUMI - Djamil, Farah Diana; Sidik, Fauzie Rahmat (Kepariwisataan: Jurnal Ilmiah, 2015)
GURILAPSS (Gunung, Rimba, Laut, Pantai, Sungai, Seni Budaya), The GURILAPS for android is a city aplication information, city guide and also introduced and promoted Sukabumi Regency of West Java Province. This application can help the local and international tourists to be able to recognize Sukabumi much more. In this application there is some information of tourism objects, travel, dining / culinary, shopping place, place of workship, medical center, the local police assistance, and much more about Sukabumi, According to the assessment of the application via rating, it can be concluded that the application are easy to understand which is stated by 90% of the user, and still need some additional information which is stated by 10% of user. Information System of Industrial Map provides information to the users about image, routes, and detail location via android devices. Keywords: Tourism, Sukabumi Regency, GURILAPSS Application, Android